Effect of in utero hydroxychloroquine exposure on the development of cutaneous neonatal lupus erythematosus. Issue 12 (8th October 2018) - Barsalou, Julie; Costedoat-Chalumeau, Nathalie; Berhanu, Adey; Fors-Nieves, Cesar; Shah, Ummara; Brown, Patrick; Laskin, Carl A; Morel, Nathalie; Levesque, Kateri; Buyon, Jill P; Silverman, Earl D; Izmirly, Peter M
Abstract : Objective: Cutaneous neonatal lupus (cNL) occurs in possibly 5%–16% of anti-Ro±anti-La antibody–exposed infants. Data suggest in utero exposure to hydroxychloroquine (HCQ) may prevent cardiac NL. The aim was to assess whether in utero exposure to HCQ decreases the risk of cNL and/or delays onset. Methods: A multicentre case–control study was performed with 122 cNL cases and 434 controls born to women with a rheumatological disease who had documentation of maternal anti-Ro±anti-La antibodies at pregnancy and confirmation of medication use and the child's outcome. A secondary analysis was performed on 262 cNL cases, irrespective of maternal diagnosis, to determine if HCQ delayed time to cNL onset. Results: Twenty (16%) cNL cases were exposed to HCQ compared with 146 (34%) controls (OR 0.4 (95% CI 0.2 to 0.6); p<0.01). Exposure to HCQ was associated with a reduced risk of cNL; exposure to anti-La antibody and female gender were associated with an increased risk of cNL. Exposure to HCQ remained significantly associated with a reduced cNL risk in the analyses limited to mothers with systemic lupus erythematosus and those who developed rash ≤1 month. When analysing all 262 cNL cases, HCQ-exposed infants were older (6.0 (95% CI 5.7 to 6.3) weeks) at cNL onset versus HCQ-non-exposed infants (4.4 (95% CI 3.9 to 5.0) weeks), but the difference was not statistically significant (p=0.21). Conclusion: Exposure to HCQ was associated with a reduced risk of cNL. Among cNL cases, those exposed to HCQ tend to have later onset of rash. Both findings suggest a protective effect of HCQ on cNL.